2021
DOI: 10.3390/su13073772
|View full text |Cite
|
Sign up to set email alerts
|

A Study on the Impact of STEAM Education for Sustainable Development Courses and Its Effects on Student Motivation and Learning

Abstract: In 2019, the United Nations released its 10-year policy of “ESD for 2030”. Many schools around the world have actively participated in the transformation and have included the United Nations Sustainable Development Goals (SDGs) in Education for Sustainable Development (ESD). Many developed countries hope to combine the concept of STEAM education (Science, Technology, Engineering, Art, and Mathematics) with interdisciplinary learning, and apply it to ESD. This study intended to integrate the sustainability conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(57 citation statements)
references
References 78 publications
(84 reference statements)
1
35
0
2
Order By: Relevance
“…According to English ( 2017 ), STEAM education is a teaching method that focuses on heightening each student’s interest in each discipline by increasing their expression, innovation, and aesthetic perception capabilities (Taylor, 2016 ), of which innovation is the most important (Hsiao & Su, 2021 ). In the United States, STEM became a national priority imitated by the National Science Foundation for all levels of secondary education (Sanders, 2009 ), whose goal was to provide students with critical thinking skills that had the potential to make students creative thinking problem solvers who would eventually be marketable in the workforce (White, 2014 ).…”
Section: Review Of the Literaturementioning
confidence: 99%
“…According to English ( 2017 ), STEAM education is a teaching method that focuses on heightening each student’s interest in each discipline by increasing their expression, innovation, and aesthetic perception capabilities (Taylor, 2016 ), of which innovation is the most important (Hsiao & Su, 2021 ). In the United States, STEM became a national priority imitated by the National Science Foundation for all levels of secondary education (Sanders, 2009 ), whose goal was to provide students with critical thinking skills that had the potential to make students creative thinking problem solvers who would eventually be marketable in the workforce (White, 2014 ).…”
Section: Review Of the Literaturementioning
confidence: 99%
“…ICT use can enhance students' motivation as well. Hsiao and Su (2021) suggested that as learning motivation, referring to a kind of attitude in which students naturally and willingly participate in learning towards the teaching goal and the internal psychological process set by the teachers, plays a significant role in a learning process, consequently, teachers can use diverse technological devices to increase students' learning motivation, which is a critical condition in every educational context. Instead of the tremendous benefits it gives, the use of ICT in an educational setting has some drawbacks.…”
Section: Information and Communication Technology In The English Language Instructionmentioning
confidence: 99%
“…(2015), but there is some controversy on the meaning or representation that the "A" stands for. Primarily it stands for Arts as the creative bit but it does not mean the other subjects lack creative thinking or creative problem-solving (Perignat & Katz-Buonincontro, 2019;Grecca et al 2021;Leroy & Romero, 2021;Hsiao & Su, 2021).…”
Section: Relation Between 21st-century Skills and Steammentioning
confidence: 99%